Negative Thermal Expansion over a Wide Temperature Range in Fe-Doped MnNiGe Composites - Zhao, Wenjun; Sun, Ying; Liu, Yufei; Shi, Kewen; Lu, Huiqing; Song, Ping; Wang, Lei; Han, Huimin; Yuan, Xiuliang; Wang, Cong (Frontiers in Chemistry, 2018)
Fe-doped MnNiGe alloys were successfully synthesized by solid-state reaction. Giant negative thermal expansion (NTE) behaviors with the coefficients of thermal expansion (CTE) of -285.23×10-6 K-1 (192-305 K) and -1167.09×10-6 K-1 (246-305 K) have been obtained in Mn0.90Fe0.10NiGe and MnNi0.90Fe0.10Ge, respectively. Furthermore, these materials were combined with Cu in order to control the NTE properties. The results indicate that the absolute value of CTE gradually decreases with increasing Cu contents. In Mn0.92Fe0.08NiGe/x%Cu, the CTE gradually changes from -64.92×10-6 K-1 (125-274 K) to -4.73×10-6 K-1 (173-229 K) with increasing value of x from 15 to 70. The magnetic measurements reveal that the NTE behaviors in this work are strongly correlated with the process of the magnetic phase transition and the introduction of Fe atoms could also change the spiral anti-ferromagnetic (s-AFM) state into ferromagnetic (FM) state at low temperature. Our study launches a new candidate for controlling thermal expansion properties of metal matrix materials which could have potential application in variable temperature environment.